2014
DOI: 10.1021/ct400626b
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Artifacts in Ewald Simulations of Inhomogeneous Systems with a Net Charge

Abstract: Ewald summation, which has become the de facto standard for computing electrostatic interactions in biomolecular simulations, formally requires that the simulation box is neutral. For non-neutral systems, the Ewald algorithm implicitly introduces a uniform background charge distribution that effectively neutralizes the simulation box. Because a uniform distribution of counter charges typically deviates from the spatial distribution of counterions in real systems, artifacts may arise, in particular in systems w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
233
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(236 citation statements)
references
References 51 publications
3
233
0
Order By: Relevance
“…In ongoing work we are working with colleagues to develop a more accurate force field to represent specific DNA sequences. We predict that this intercalation will alter the structure of the DNA duplex, and therefore have the potential to affect the biological functions of DNA including the inhibition of transcription, replication, and DNA repair processes [40]. Therefore, excess E2 has the potential to exert some serious side effects such as disruption of ER-DNA binding, DNA damage and possibly the initiation of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ongoing work we are working with colleagues to develop a more accurate force field to represent specific DNA sequences. We predict that this intercalation will alter the structure of the DNA duplex, and therefore have the potential to affect the biological functions of DNA including the inhibition of transcription, replication, and DNA repair processes [40]. Therefore, excess E2 has the potential to exert some serious side effects such as disruption of ER-DNA binding, DNA damage and possibly the initiation of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Our simulations do not have explicit ions in the system rather a neutralizing background charge is applied [40]. We examine the effect of neutralizing background charge by simulating one of the bound complexes of E2 to erDNA with 34 explicit Na + ions.…”
Section: Methodsmentioning
confidence: 99%
“…Long ranged forces (Coulomb interactions) were handled by Ewald sum techniques [62], using a uniform neutralizing background charge in all cases. This is satisfactory enough for a system including a small charge as the lone proton, whereas in extended systems such as proteins of membranes in water, it has been reported that the use of a counterion would be in order [63].…”
Section: Methodsmentioning
confidence: 99%
“…The dipole moment values of dialanine prepared with additional charges span the intervals (4,14), (9,21) and (19,38) D for the cases with ±0.3 e, ±0.5 e and ±1.0 e, respectively. Note that a dipole moment of 9 D (the average value for the case with ±0.3 e) or, equivalently, a moment of 0.9 D per heavy atom, is a value not far from the average for the structures in the PDB.…”
Section: A Preparation Of the Systems And MD Simulationsmentioning
confidence: 99%
“…This is not allowed when doing the usual one-protein simulation with Ewald, since a change in protein-protein distance is strictly forbidden. Ewald artifacts (inaccuracies created by the use of artificial periodicity) were studied before, [4][5][6] but it was Weber and McCammon 7 who specifically studied the problem presented here: due to the computational power available at the time, it was difficult to clearly distinguish between the different minima in the dialanine free energy space, hence leading to the neglect of the effects of this particular issue.…”
Section: Introductionmentioning
confidence: 99%